Analisis Yuridis Atas Tenaga Keperawatan Yang Melakukan Pelecehan Seksual Kepada Pasien - Dhian Yuli Prasetyo (Universitas Islam Indonesia, 2020)
This study discusses two problems: First, what is the basis for the policy of sexual harassment by nursing staff against patients in statutory regulations; and second, what is the urgency of lex specialis in criminal governance for nursing staff who sexually abuse patients. This study uses a normative juridical method with a statutory approach. Data collection was carried out by literature study with qualitative analysis. The results of the study concluded that: First, the policy on the criminal act of sexual harassment by nursing staff against patients still applies the general legal rules to decide on perpetrators who have the nursing profession, namely based on Article 290 paragraph (1) of the Criminal Code; and Second, the urgency of the lex specialis in regulating criminal acts of sexual harassment by nursing personnel against patients is because the existing regulations have not been able to fully address the problem of sexual harassment, especially in the protection of victims.